Adaptations of skeletal muscle to prolonged, intense endurance training - Hawley, J. A. (Clinical and Experimental Pharmacology and Physiology, 2002)
1. Endurance exercise induces a variety of metabolic and morphological responses/adaptations in skeletal muscle that function to minimize cellular disturbances during subsequent training sessions. 2. Chronic adaptations in skeletal muscle are likely to be the result of the cumulative effect of repeated bouts of exercise, with the initial signalling responses leading to such adaptations occurring after each training session. 3. Recently, activation of the mitogen-activated protein kinase signalling cascade has been proposed as a possible mechanism involved in the regulation of many of the exercise-induced adaptations in skeletal muscle. 4. The protein targets of AMP-activated protein kinase also appear to be involved in both the regulation of acute metabolic responses and chronic adaptations to exercise. 5. Endurance training is associated with an increase in the activities of key enzymes of the mitochondrial electron transport chain and a concomitant increase in mitochondrial protein concentration. These morphological changes, along with increased capillary supply, result in a shift in trained muscle to a greater reliance on fat as a fuel with a concomitant reduction in glycolytic flux and tighter control of acid-base status. Taken collectively, these adaptations result in an enhanced performance capacity.